Unmanned aerial vehicle for forest fire extinguishing - LIU BOWEN; MIAO BINGDI; GUO MAOSHENG (2021)
The utility model discloses an unmanned aerial vehicle for forest fire extinguishing, which comprises an unmanned aerial vehicle body, a battery assembly fixed on the unmanned aerial vehicle body, four wings connected with the unmanned aerial vehicle body, and a communication antenna arranged on the unmanned aerial vehicle body and used for receiving flight control signals and transmitting data, the fire extinguishing bomb storage box is fixed at the lower part of the unmanned aerial vehicle body and is used for storing fire extinguishing bombs; the fire extinguishing bomb storage box comprises a rack arranged at the bottom of the lower portion of the unmanned aerial vehicle body, a storage box fixed in the rack, provided with an opening in the lower portion and used for storing fire extinguishing bombs, and a throwing driving mechanism arranged on the rack and used for opening and closing the opening in the lower portion of the storage box. By means of the scheme, the fire extinguishing device has the advant